2016
DOI: 10.1038/srep36406
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bacteriome associated with Phlebotomus chinensis (Diptera: Psychodidae) sand flies in two wild populations from China

Abstract: Sand fly Phlebotomus chinensis is a primary vector of transmission of visceral leishmaniasis in China. The sand flies have adapted to various ecological niches in distinct ecosystems. Characterization of the microbial structure and function will greatly facilitate the understanding of the sand fly ecology, which would provide critical information for developing intervention strategy for sand fly control. In this study we compared the bacterial composition between two populations of Ph. chinensis from Henan and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 67 publications
(71 reference statements)
2
29
1
Order By: Relevance
“…Three of these new genera -Pluralibacter, Pseudocitrobacter, and Rosenbergiella -belong to the Enterobacteriaceae. Pluralibacter was recently differentiated from the Enterobacter genus (Brady et al, 2013) and was also found in the sand fly Phlebotomus chinensis Newstead (Li et al, 2016), the Mediterranean fruit fly (medfly), C. capitata (Papanicolaou et al, 2016), and the mosquito Anopheles albimanus Wiedemann (Dada et al, 2018). In contrast, Pseudocitrobacter and Rosenbergiella have never been reported as insect gut microbes before.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these new genera -Pluralibacter, Pseudocitrobacter, and Rosenbergiella -belong to the Enterobacteriaceae. Pluralibacter was recently differentiated from the Enterobacter genus (Brady et al, 2013) and was also found in the sand fly Phlebotomus chinensis Newstead (Li et al, 2016), the Mediterranean fruit fly (medfly), C. capitata (Papanicolaou et al, 2016), and the mosquito Anopheles albimanus Wiedemann (Dada et al, 2018). In contrast, Pseudocitrobacter and Rosenbergiella have never been reported as insect gut microbes before.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bacteria identified by sequencing a 16S rDNA clone library obtained from the gut contents of adult females of this species were found to be from the families Coxiellaceae, Enterobacteriaceae mostly from the genus Enterococcus , and Pseudomonadaceae mostly from the genus Pseudomonas . Additionally, the intracellular Diplorickettsia , Rickettsia , Rickettsiella , Spiroplasma and Wolbachia were identified with these methods in the same study (Li et al , 2016 ). Curiously, Rickettsia and Wolbachia were found only in sand flies collected from a locality where anthroponotic visceral leishmaniasis occurs and dogs and other animals are the reservoirs (Li et al , 2016 ).…”
Section: Sand Fly Microbiotamentioning
confidence: 97%
“…Additionally, the intracellular Diplorickettsia , Rickettsia , Rickettsiella , Spiroplasma and Wolbachia were identified with these methods in the same study (Li et al , 2016 ). Curiously, Rickettsia and Wolbachia were found only in sand flies collected from a locality where anthroponotic visceral leishmaniasis occurs and dogs and other animals are the reservoirs (Li et al , 2016 ). Diplorickettsia , Rickettsiella and Spiroplasma were found only in sand flies collected from a locality where zoonotic visceral leishmaniasis occurs and humans are the identified reservoirs.…”
Section: Sand Fly Microbiotamentioning
confidence: 97%
“…Many sand y species are known to rely on a broad range of species for blood meals (19,20,(27)(28)(29) , typically mammals (20,(30)(31)(32)(33) but also various cold-blooded animals (21). In this study, we investigated the blood sources of sand ies by ampli ed speci c animal's mtDNA cyt b fragments using PCR.…”
Section: Discussionmentioning
confidence: 99%